Abusive Language Analysis of Netizen Comments on Gus Miftah’s Instagram Account - Salsabila, Salsabila; Syahputra, Bambang Panca (Journal of English Language and Education, 2025)
This study discusses the analysis of abusive language on Gus Miftah's Instagram account that is concerned on investigating the type of abusive language in netizen communication on Gus Miftah Instagram account. The objective of this study is to determine the types of abusive language and explain the process of abusive language used in the comment column of Gus Miftah's Instagram account. This study uses a descriptive qualitative method. The source of the data was obtained from comments of netizen and it was collected by looking at the Instagram comments and taking a note, and the data were analyzed by some steps they were data reduction, data display, drawing and verifying conclusion.  There were 100 abusive languages were found in this study. The data was analyzed by identifying comments into 10 types of abusive language, classifying utterances into each type of abusive language. There were 9 types of abusive language were found in the comment column of Gus Miftah's Instagram account, namely Animals Name, Part of body, Profession, Activity, Adjective, Supernatural Creature, Noun, Kinship, and Foreign Language